Industry 4.0 and Current Competencies - Eva Beke; Richard Horvath; Katalin Takacs-Gyorgy (Naše gospodarstvo/Our economy, 2020)
There is a growing gap between higher education systems and the needs and demands of the labor market. Many of today’s students will work at jobs that just have emerged or do not even exist yet. The “newcomers” will need both digital and social-emotional skills in the coming years. These new competen- cies will make the new generation of employees’ company goals. This article presents the results of the recent research about modern-day competencies to evaluate what exactly relevant companies’ expectations are, how students see their knowledge and value in future workplaces, and how academia is coping with this new demand. For this analysis, I have conducted deep in- terviews with applicable entities, namely companies from the car industry and from the field of security industries (cyber security, integrated camera surveillance, financial security) to see how Industry 4.0 shapes the competen- cies they expect from our students entering to the job market. Engineering students - by questionnaire -were also interviewed at the Óbuda University, to examine their views about the skills gained at the university and how these competencies helping them to apply for the right position in the job market. Although the competence list showed similarities in the expected skill sets, the order of them differs. While most companies are aiming to hire team players with creative problem solving and those are capable and willing to accept changes, the students’ observations showed that technical skills, ex- pertise, and problem solving are the most important competencies for future employment. Based on all participants’ answers and additional research, we aim to involve international companies to take part in our higher education system more thoroughly either by widening the practical in-site education or by inviting them to our university for lecturing future engineers. Furthermore, new courses are introduced at our university, such as information security, humanitarian response management, rehabilitation environmental planning engineering or ergonomics and human factors specialization.